2015
DOI: 10.1155/2015/372375
|View full text |Cite
|
Sign up to set email alerts
|

Meningitis, Clinical Presentation of Tetanus

Abstract: Background. Tetanus is an acute disease caused by a neurotoxin produced by Clostridium tetani. Tetanus immunization has been available since the late 1930s but sporadic cases still occur, usually in incompletely vaccinated or unvaccinated individuals. Case Report. An elderly previously vaccinated female contracted tetanus following foot injury. Clinically she presented with meningitis causing diagnostic and therapeutic delays. Why Should Physician Be Aware of This? Even in developed countries the differential … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 9 publications
(9 reference statements)
0
4
0
Order By: Relevance
“…Other conditions that may have similar clinical manifestations are meningitis/encephalitis, rabies, and acute intraabdominal processes (due to a stiff abdomen). Increased tone in the central muscles (face, neck, back and abdomen) accompanied by generalized spasm that becomes subtle and symptom-free in the hands and feet, strongly supports the presence of tetanus (2,16,17).…”
Section: Table 2 Ablett Classification Of Severity Of Tetanus (14)mentioning
confidence: 76%
“…Other conditions that may have similar clinical manifestations are meningitis/encephalitis, rabies, and acute intraabdominal processes (due to a stiff abdomen). Increased tone in the central muscles (face, neck, back and abdomen) accompanied by generalized spasm that becomes subtle and symptom-free in the hands and feet, strongly supports the presence of tetanus (2,16,17).…”
Section: Table 2 Ablett Classification Of Severity Of Tetanus (14)mentioning
confidence: 76%
“…Since the present study comprised of neuroinvasive bacteria based on a literature search that has shown few reports of meningitis caused by B. cereus and Cl. tetani [ 39 , 40 ], the present study demonstrated that it is not mandatory for bacteria to cross the blood brain barrier (BBB) to affect the neurotransmission in CNS. Entry of bacteria into any part of body has distant effect implications.…”
Section: Discussionmentioning
confidence: 90%
“…The research results of Dai Cheng [12] showed that the mortality rate of patients who underwent standard wound debridement was signi cantly lower than that of those who did not. A common feature can also be found in many reports of tetanus: the wounds after contamination were not treated with timely standard debridement [13][14][15][16][17] . Therefore, standardized wound management is very necessary.…”
Section: Discussionmentioning
confidence: 99%